KEMAMPUAN PUBLIC SPEAKING MAHASISWA ILMU KOMUNIKASI HINDU PADA PROSES PERKULIAHAN - Talia, Nova; Edung, Tardi; Darsana, I Made (Dharma Duta, 2025)
This study aims to provide an overview of the public speaking skills of Hindu Communication Science students during the learning process. The research focuses on three main questions: (1) How are the public speaking abilities of Hindu Communication Science students during lectures? (2) What challenges do they encounter in the learning process? (3) How do they overcome public speaking challenges? The study applies public speaking theory and interpersonal communication theory as its theoretical foundation. A qualitative approach was used, employing techniques such as observation, interviews, and documentation. The data analysis process consisted of four stages: data collection, data reduction, data presentation, and verification or conclusion. The results show that most students demonstrate moderately good public speaking skills, particularly in expressing opinions, delivering material, and participating in classroom discussions. Factors such as interactive learning environments, involvement in student organizations, and support from lecturers contribute positively to skill development. However, students still face several challenges, including nervousness, lack of confidence, and difficulty in organizing messages systematically. Internal factors like anxiety and limited literacy, as well as external factors such as an unsupportive communication environment, also affect their performance. To address these challenges, students engage in regular practice, prepare their materials thoroughly, and apply nonverbal communication techniques effectively.